The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.18231/j.ijohd.2020.009
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between depression and periodontal health: A clinical study done among outpatients at Seema Dental College and Hospital, Rishikesh

Abstract: Background: Chronic periodontitis is a multifactorial disease which is influenced by a variety of risk factors including psychosocial factors such as depression and stress that are known to affect the immune system thereby affecting the periodontal tissue. Aim: The aim of this study was to evaluate the association between periodontal parameters and depression. Materials and Methods: 35 patients with periodontitis as test group and 35 periodontally healthy patients as control group were included. Oral hygiene i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(11 reference statements)
1
0
0
Order By: Relevance
“…10 The finding of current study are in agreement with study of Penmetsa et al which found dental students with high stress levels than medical and pharmacy students 7 Moss et al stated that depression was related to increased severity of periodontitis. 11 Their results are in line with our study as depression seemed to have strongest relationship with chronic localized periodontitis as can be observed in Table 1.…”
Section: Discussionsupporting
confidence: 91%
“…10 The finding of current study are in agreement with study of Penmetsa et al which found dental students with high stress levels than medical and pharmacy students 7 Moss et al stated that depression was related to increased severity of periodontitis. 11 Their results are in line with our study as depression seemed to have strongest relationship with chronic localized periodontitis as can be observed in Table 1.…”
Section: Discussionsupporting
confidence: 91%